Pengembangan Muhammdiyah dalam Membangun Moderasi Beragama di Kabupaten Karo Sumatera Utara - Rahman, Rizki Fachru; Lubis, Dahlia; Ekowati, Endang (Lembaga Yasin AlSys, 2024)
This research aims to determine the development of Muhammadiyah in building religious moderation in Karo Regency, North Sumatra. The aim of this research is to find out the extent to which Muhammadiyah residents understand Religious Moderation and the views of Muhammadiyah Karo Regency regarding Religious Moderation. This research method uses a qualitative approach. By using data collection techniques through interviews, observation and documentation. The informants in this research were the Muhammadiyah Regional Leadership of Karo Regency, the Muhammadiyah Autonomous Organization, and Sympathizers. The results of the research show that Religious Moderation does not understand Muhammadiyah residents due to a lack of knowledge except for Muhammadiyah Regional Leaders or Ortoms in Karo Regency. The Muhammadiyah community and sympathizers think that they don't know what Religious Moderation is, but in carrying out social activities they respect each other's differences as long as they don't violate Islamic rules.